Pengaruh Live Streaming, Affiliate Marketing, dan Perceived Price terhadap Purchase Decision yang Dimediasi oleh Customer Trust pada TikTok Shop: Studi pada Mahasiswa Aktif Universitas Proklamasi 45 - Tria Lady Sijabat; Djoko Wijono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of live streaming, affiliate marketing, and perceived price on purchase decisions with customer trust as a mediating variable among students of Universitas Proklamasi 45. This study used a quantitative approach with a purposive sampling technique to determine 100 respondents relevant to the research criteria. The research instrument in the form of a structured questionnaire was distributed to obtain primary data, then analyzed using the Partial Least Squares (PLS) path model as a statistical analysis method. The results showed that the variables of live streaming, affiliate marketing, and perceived price simultaneously had a positive and significant effect on customer trust. Furthermore, customer trust was proven to have a significant influence on purchase decisions, thus understanding that customer trust is an important factor in driving purchase decisions. However, other results showed that live streaming did not directly influence purchase decisions. However, when mediated by customer trust, the influence of live streaming on purchase decisions became significant. These findings provide theoretical contributions to the development of digital marketing science, particularly in understanding the mediating role of customer trust in consumer behavior. In addition, practical implications for business actors are the importance of building consumer trust through live streaming strategies, affiliate marketing, and appropriate price offers to improve purchase decisions.